2013
DOI: 10.1016/j.molonc.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of the HepG2 genome by long interspersed nuclear element‐1

Abstract: Long Interspersed Nuclear Element-1 (LINE-1 or L1) is an autonomous, mobile element within the human genome that transposes via a "copy and paste" mechanism and relies upon L1-encoded endonuclease and reverse transcriptase (RT) activities to compromise genome integrity. L1 has been implicated in various forms of cancer, but its role in the regulation of the oncogenic phenotype is not understood. The present studies were conducted to evaluate mechanisms of genetic regulatory control in HepG2 cells by human L1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…An excellent example of this comes from the participation of L1 in X chromosome inactivation during embryo development. 64 In a HepG2 cell line, 65 ectopic L1 expression resulted in detectable expression changes of 24 genes, with half of them being retrotransposition-independent.…”
Section: Functions Of L1s In Cancer Retrotransposition-dependent Funcmentioning
confidence: 99%
“…An excellent example of this comes from the participation of L1 in X chromosome inactivation during embryo development. 64 In a HepG2 cell line, 65 ectopic L1 expression resulted in detectable expression changes of 24 genes, with half of them being retrotransposition-independent.…”
Section: Functions Of L1s In Cancer Retrotransposition-dependent Funcmentioning
confidence: 99%
“…Cloning of vectors pB001 CTR (vector backbone or CTR), pB016 MUT (Aspartate (D) to Tyrosine (Y) mutant at position 702 (D702Y)) and pB015 WT (Wildtype or WT) were done as described in Bojang et al 2013 [30]. These vectors were used to generate stable transfected HepG2 cell lines used to monitor retrotransposition activity of L1 RP .…”
Section: Methodsmentioning
confidence: 99%
“…The integration of L1 sequences near genes can modulate their expression, induce alternative splicing, reshuffle the genome causing inter-individual genetic variations and/or lead to epigenetic dysregulation at the insertion site [25, 26, 27]. Within this context, we recently showed that forced expression of L1 RP , an active L1 isolated from exon 1 of the retinitis pigmentosa gene (RP) of a patient with X-linked retinitis pigmentosa [28, 29], modulates genetic networks involved in the regulation of inflammation, adhesion and cellular metabolism in HepG2 cells [30]. The HePG2 cell line is frequently used because it retains high functional activity of liver-specific genes [31, 32].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations